Salivary oxidant/ antioxidant status and hematological parameters in patients with recurrent aphthous stomatitis - Neda Babaee; Hamed Hosseinkazemi; Mahdi Pouramir; Oveis Khakbaz-Baboli; Maede Salehi; Fatemeh Khadir; Ali Bijani; Mahsa Mehryari (Babol University of Medical Sciences, 2016)
Background: Recurrent aphthous stomatitis (RAS) is the most common inflammatory ulcerative condition of oral cavity. The aim of this study was to compare the levels of the salivary Malondialdehyde (MDA) and total antioxidant capacity (TAC) and blood parameter in RAS versus healthy controls. Methods: This case-control study consisted of 28 patients with RAS and 28 age and sex -matched control without RAS. Cell blood count was assessed by sysmex system, serum iron and total iron binding capacity was measured by standard laboratory kit and for ferritin ELISA kit was utilized. Salivary TAC and MDA level determined using FRAP and TBARS method respectively. Statistical analysis was performed using SPSS Version 21, chi-square test was used to compare proportions, and student’s t-test and Mann Whitney U-test were used for the comparison of quantitative variables Results: Salivary MDA level was significantly higher (p<0.001) and TAC level was significantly lower (p<0.042) in RAS as compared with the control group. Also, serum ferritin level was significantly higher in RAS patients (p<0.008). Conclusion: These findings indicate the alteration of oxidant/antioxidant status was observed in recurrent aphthous stomatitis, may be also associated with changing several hematinic parameters in this study. The finding maybe helpful to clarify the etiologies of RAS and possibely to improve the management or preventive options.